THE OVERALL APPROACH TO THE OPTIMIZATION OF THE PRODUCTION TECHNOLOGY OF SHEET BLANKS - Moroz, M. M.; Drahobetskyi, V. V.; Markevych, A. H. (Science and Transport Progress, 2009)
The technological process of cutting the sheet metal as a set of technological processes divided on subsets is considered. The classification of technological processes of preparation production and the criterion of optimality with the search purpose of optimum technological process of producing the sheet bars are offered.